Pelatihan Roasting Kopi Untuk Membangun Minat Wirausaha Pada Pemuda di Kota Banda Aceh - Nurulia Dimitha; Furqansyah, M. Danil; Arami, Iwan (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Coffee has many benefits that can be processed and has high economic value. That way, to be able to maximize the benefits of the coffee beans, you must maximize every process in the coffee so as not to reduce the quality of the coffee beans. So with the increasing increase in coffee roasting, high quality has become the standard in every existing coffee roaster. This service activity was carried out at Aqilla Coffee and Roastery, Ulee Kareng District, Banda Aceh City. The aim of this service is to provide training, knowledge and skills to young people in Banda Aceh City regarding processing coffee beans into coffee powder with high selling value to increase interest in entrepreneurship. The expected output from this community service activity is to increase the knowledge of young people in Banda Aceh City about the procedures for processing coffee beans into coffee powder, foster interest in entrepreneurship in improving soft skills as an effort to improve the economy, increase the benefits and added value of a product for economic activities, and as academics, the results of this activity will be published in a journal.